The role of IL-6 in coronavirus, especially in COVID-19 - Wang, Xinyi; Tang, Guozheng; Liu, Yuchen; Zhang, Lizhi; Chen, Bangjie; Han, Yanxun; Fu, Ziyue; Wang, Liuning; Hu, Guangzhi; Ma, Qing; Sheng, Shuyan; Wang, Jianpeng; et al. (Frontiers in Pharmacology, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infects both people and animals and may cause significant respiratory problems, including lung illness: Corona Virus Disease 2019 (COVID-19). Swabs taken from the throat and nose of people who have the illness or are suspected of having it have shown this pathogenic virus. When SARS-CoV-2 infects the upper and lower respiratory tracts, it may induce moderate to severe respiratory symptoms, as well as the release of pro-inflammatory cytokines including interleukin (IL)-6. COVID-19-induced reduction of IL-6 in an inflammatory state may have a hitherto undiscovered therapeutic impact. Many inflammatory disorders, including viral infections, has been found to be regulated by IL-6. In individuals with COVID-19, one of the primary inflammatory agents that causes inflammatory storm is IL-6. It promotes the inflammatory response of virus infection, including the virus infection caused by SARS-CoV-2, and provides a new diagnostic and therapeutic strategy. In this review article, we highlighted the functions of IL-6 in the coronavirus, especially in COVID-19, showing that IL-6 activation plays an important function in the progression of coronavirus and is a rational therapeutic goal for inflammation aimed at coronavirus.